Upaya Peningkatan Volume Penjualan melalui Optimalisasi Kualitas Produk dan Saluran Distribusi - Delly Aulia; Rahmat Hidayat (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study was to determine the effect of product quality and distribution channels on sales volume in SMEs. The sample of this study were 34 traders who redistributed the product, the sample was taken using a census sampling technique, namely the sampling technique when all members of the population are used as samples, the data analysis method used in this research is descriptive quantitative, while the data analysis model used in this research is multiple linear regression analysis. Testing this hypothesis using the coefficient of determination test (R2), partial test (t test) and simultaneous test (F test). The results of this study indicate that partially and simultaneously product quality and distribution channels have a significant effect on sales volume.